2014
DOI: 10.1016/j.sjopt.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Corneal spherical aberration and its impact on choosing an intraocular lens for cataract surgery

Abstract: Customized selection of aspheric IOLs based on the eyes' corneal spherical aberration has no significant importance comparing their results with the non-selected group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 26 publications
5
17
0
Order By: Relevance
“…In this study, no significant differences in postoperative UCVA and BCVA were observed between the two groups, which were consistent with the findings of previous controlled studies related to customized selection [13,14,22,23]. The finding of the mean corneal SA at 6mm PD was comparable to that in the study by Beiko et al [2] (0.28μm vs 0.27μm), and the unchanged corneal SA after surgery indicated that a bias resulting from the surgical impacts on corneal SA could be avoided.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, no significant differences in postoperative UCVA and BCVA were observed between the two groups, which were consistent with the findings of previous controlled studies related to customized selection [13,14,22,23]. The finding of the mean corneal SA at 6mm PD was comparable to that in the study by Beiko et al [2] (0.28μm vs 0.27μm), and the unchanged corneal SA after surgery indicated that a bias resulting from the surgical impacts on corneal SA could be avoided.…”
Section: Discussionsupporting
confidence: 93%
“…Previous non-controlled studies reported that applying a customized selection of aspheric IOL implantation based on corneal SA could precisely reduce the postoperative ocular SA closest to zero [11,12]. However, the current limited controlled studies merely measured SA or contrast sensitivity for assessing the visual quality, and there is still a lack of consensus whether optical quality following 4 a customized selection with a target ocular SA of zero differs from that following a non-customized selection [13,14]. In this study, we applied a random selection strategy in the control group, by which we aimed to replicate the aspheric IOL selection strategy that we have been using in actual clinical practice in the past.…”
Section: Introductionmentioning
confidence: 98%
“…When comparing our results with those ones from other studies with other widely used monofocal IOLs, we found comparable values about CS and VF-14. 15,16 This preliminary study validates the visual performance of either I-Stream H and CT Lucia 211P, and highlights their good profile of safety. This is a crucial aspect to consider when evaluating a new medical device introduced into the market.…”
Section: Discussionsupporting
confidence: 61%
“…The availability of various aspheric IOL designs has enabled the customized selection to precisely achieve a postoperative target ocular SA of zero, which has been considered to be the optimal SA value for producing the best optical quality and visual performance by some researchers [ 20,21]. However, there are few controlled studies on optical quality of customized selection with a target SA of zero and the conclusions are inconsistent [ 13,14]. The present study aimed to comprehensively compare the postoperative optical quality using a combination of Hartmann-shack wavefront aberrometer and double-pass instrument between customized and random selections of aspheric IOLs, which has been rarely applied in previous studies regarding the customized selection with a target ocular SA of zero.…”
Section: Discussionmentioning
confidence: 99%
“…Previous non-controlled studies reported that applying a customized selection of aspheric IOL implantation based on corneal SA could precisely reduce the postoperative ocular SA closest to zero [ 11,12]. However, the current limited controlled studies merely measured SA or contrast sensitivity for assessing the visual quality, and there is still a lack of consensus whether optical quality following a customized selection with a target ocular SA of zero differs from that following a non-customized selection [ 13,14]. In this study, we applied a random selection strategy in the control group, by which we aimed to replicate the aspheric IOL selection strategy that we have been using in actual clinical practice in the past.…”
mentioning
confidence: 98%